2020
DOI: 10.1016/j.jallcom.2020.154547
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and high potential of 3D metal–organic framework (MOF) nanoparticles for curing with epoxy

Abstract: In this study, the potential of microporous 3D metal-organic framework (MOF) for curing epoxy resin has been discussed. First, MIL-101 (Cr), a chromium based MOF, was synthesized under hydrothermal condition and then characterized by using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD) and thermogravimetric (TGA) measurements. Epoxy nanocomposites containing 0.1, 0.3 and 0.5 wt.% of MOF nanocrystals were subsequently prepared and their curability was studied in terms of the universal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 61 publications
0
61
0
Order By: Relevance
“…The broad peak appeared irrespective of sample type in the thermograms of samples, which can be considered as a double-peaked curve, where the smaller shoulder overlaps To make an inclusive assessment, we need a powerful measure that integrates all the factors affecting the whole cure process into a simple criterion, known as Cure Index (CI). The applicability and versatility of the CI have been repeatedly proved in previous works [29,30]. To calculate such a measure, one should consider the following equations [10]: Placing the data in Table 1 under scrutiny, it has been demonstrated that the introduction of AHP nanoparticles to the epoxy matrix has contributed to cure reactions of epoxy resin, for all the CI values are laid in Good and Excellent cure states.…”
Section: Qualitative Cure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The broad peak appeared irrespective of sample type in the thermograms of samples, which can be considered as a double-peaked curve, where the smaller shoulder overlaps To make an inclusive assessment, we need a powerful measure that integrates all the factors affecting the whole cure process into a simple criterion, known as Cure Index (CI). The applicability and versatility of the CI have been repeatedly proved in previous works [29,30]. To calculate such a measure, one should consider the following equations [10]: Placing the data in Table 1 under scrutiny, it has been demonstrated that the introduction of AHP nanoparticles to the epoxy matrix has contributed to cure reactions of epoxy resin, for all the CI values are laid in Good and Excellent cure states.…”
Section: Qualitative Cure Analysismentioning
confidence: 99%
“…To make an inclusive assessment, we need a powerful measure that integrates all the factors affecting the whole cure process into a simple criterion, known as Cure Index (CI). The applicability and versatility of the CI have been repeatedly proved in previous works [29,30]. To calculate such a measure, one should consider the following equations [10]:…”
Section: Qualitative Cure Analysismentioning
confidence: 99%
“…The vulcanization reaction of a rubber compound can be evaluated through using a differential equation on the basis of time and temperatures of the reaction as the following equation [ 16 , 17 , 18 ]: where α is the degree of cure, dα/dt is the curing rate, t is time, K is the kinetic constant at temperature T and f(α) is function related to the adopted model. The degree of cure parameter is defined as the following relation in the oscillating disc rheometer (ODR) analysis [ 19 ]: where M t is the torque value at time t, M 0 and M ∞ are the torque values at time zero and the end of vulcanization reaction, respectively.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The ultimate properties of cross-linkable polymers such as epoxy thermoset resin strongly depend on the formation of a completely cured network [ 17 ]. In terms of thermosetting epoxy resins, their curability in the presence of any additives and nanofillers has been key for research [ 18 , 19 ]. Therefore, the upward trend for epoxy nanocomposite exploitation necessitates research on the structure–properties correlation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%